Examining the consequences of calcium substitution on the physical properties and conduction mechanism of Y3GaO6 - Singh P.; Pandey R.; Srivastava K.K.; Singh P. (My University, 2025)
The influence of calcium doping on the Y3GaO6 system was systematically investigated for electrochemical applications. The Y3(1−x)Ca3xGaO6 (x = 0, 0.02, 0.04, 0.08, 0.12) ceramics compositions were prepared via conventional solid-state reaction route and their structural, electrical and electrochemical properties were investigated. The structural phase analysis revealed the formation of the orthorhombic phase with the Cmc21 space group. However, at higher concentrations of calcium doping, i.e. x > 0.02, a few secondary phases of Y2O3 and CaCO3 were also observed. Impedance spectra suggest an increase in the total conductivity up to x = 0.02 of Ca doping, and a decrease in the conductivity was observed for the higher concentration of Ca substitution. The substitution of Ca with x > 0.02 not only increases the oxygen vacancies rather segregates the impurities along the grain boundaries. Consequently, the impurities have negative influence on both the grain and grain-boundary conductivities. Cyclic voltammetry and Chronoamperometry studies have also been performed to characterize the samples. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.